The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/eji.200839057
|View full text |Cite
|
Sign up to set email alerts
|

Origins and functional basis of regulatory CD11c+CD8+ T cells

Abstract: Previously, we showed that CD11c defines a novel subset of CD8 1 T cells whose in vivo activity is therapeutic for arthritis; however, the mechanisms directing their development, identity of their precursors, and basis of their effector function remain unknown. Here, we show that the novel subset develops from CD11c surfaceÀ CD8 1 T cells and undergoes robust expansion in an antigen-and 4-1BB (CD137)-dependent manner. CD11c 1 CD8 1 T cells exist in naïve mice (o3%) with limited suppressive activity. Once activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…In this study, SI CD11c ϩ CD8 ϩ T cells potently induced colitis protection, compared with other studies in which effective numbers of CD8 ϩ T cells from peripheral compartments required 4-to 80-fold greater numbers (1 to 20 ϫ 10 6 cells) for colitis protection (10,28,36,46,47) or other autoimmune diseases (14,26,38,45). Both cytolytic and noncytolytic mechanisms of immunoregulation have been reported for regulatory CD8 ϩ T cells, and those displayed by SI CD11c ϩ CD8 ϩ T cells remain to be determined.…”
Section: Cd8mentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, SI CD11c ϩ CD8 ϩ T cells potently induced colitis protection, compared with other studies in which effective numbers of CD8 ϩ T cells from peripheral compartments required 4-to 80-fold greater numbers (1 to 20 ϫ 10 6 cells) for colitis protection (10,28,36,46,47) or other autoimmune diseases (14,26,38,45). Both cytolytic and noncytolytic mechanisms of immunoregulation have been reported for regulatory CD8 ϩ T cells, and those displayed by SI CD11c ϩ CD8 ϩ T cells remain to be determined.…”
Section: Cd8mentioning
confidence: 79%
“…Finally, recent studies of nonmucosal CD11c ϩ CD8 ϩ T cells reported that their suppression of inflammatory CD4 ϩ T cells required indoleamine 2,3-dioxygenase (IDO) induced by CD137 (4 -1BB), a TNF family member involved with CD28-independent T-cell activation (45). As a tryptophan-catabolizing enzyme, IDO plays a variety of important roles in immune tolerance, tumor resistance, chronic infections, and autoimmune disease (29).…”
Section: Cd8␣mentioning
confidence: 99%
“…For example, it was found that CD11c + CD8 + T cells possess higher levels of LCMVspecific killing activity than CD11c 2 CD8 + T cells (42); anti-4-1BB mAb administration to B16F10 melanoma-bearing mice induced potent expansion of CD11c + CD8 + T cells in parallel with suppression of tumors (43,44). However, CD11c high CD8 + T cells might be induced and expanded only in unique conditions, such as on day 8 of L. monocytogenes infection in this study, or after agonistic anti-4-1 BB mAb inoculation in autoimmune or inflammatory disorders (25)(26)(27).…”
Section: Cd8mentioning
confidence: 80%
“…CD11c ? T cells can be detected in the periphery and constitute \3% of the peripheral T cell population, although they appear as naïve cells (based on their CD44 and CD62L profiles) and do not present appreciable suppressive activity in vitro [103]. These cells, however, do express significantly elevated levels of CD28 and CD103 relative to their CD11c-negative counterparts.…”
Section: Cd8 ? Cd45ro ? T Cells In Humans (Allospecific)mentioning
confidence: 99%
“…T cells was not established, and the possibility of anti-4-1BB acting on other cell types was not excluded. A subsequent study by Vinay et al [103] showed that CD8 ? CD11c ?…”
Section: Cd8 ? Cd45ro ? T Cells In Humans (Allospecific)mentioning
confidence: 99%